2001
DOI: 10.1051/0004-6361:20010247
|View full text |Cite
|
Sign up to set email alerts
|

The extraordinarily bright optical afterglow of GRB 991208 and its host galaxy

Abstract: Broad-band optical observations of the extraordinarily bright optical afterglow of the intense gamma-ray burst GRB 991208 started ∼ 2.1 days after the event and continued until 4 Apr 2000. The flux decay constant of the optical afterglow in the R-band is −2.30 ± 0.07 up to ∼ 5 days, which Send offprint requests to: A. J. Castro-Tirado (ajct@laeff.esa.es)is very likely due to the jet effect, and after that it is followed by a much steeper decay with constant −3.2 ± 0.2, the fastest one ever seen in a GRB optica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(33 citation statements)
references
References 65 publications
(66 reference statements)
3
30
0
Order By: Relevance
“…In addition, two foreground absorbing systems are detected (Bloom et al 2001;Castro et al 2001). These systems are typical for the metallic line absorbers at comparable redshifts.…”
Section: Grb 010222mentioning
confidence: 96%
See 2 more Smart Citations
“…In addition, two foreground absorbing systems are detected (Bloom et al 2001;Castro et al 2001). These systems are typical for the metallic line absorbers at comparable redshifts.…”
Section: Grb 010222mentioning
confidence: 96%
“…Also, from the possible connection of GRBs with supernovae (Galama et al 1998(Galama et al , 2000Kulkarni et al 1998;Bloom et al 1999Bloom et al , 2002bReichart 1999;Castro-Tirado et al 2001;Björnsson et al 2001), we would expect that GRBs occur in dense star-forming regions; large amounts of optical extinction are then naturally expected, but only small amounts are observed (Galama & Wijers 2001).…”
Section: No 1 2003 Observations Of Grb 010222mentioning
confidence: 96%
See 1 more Smart Citation
“…Earlier evidence on the GRB-SN connection was initially based on the coincidence of GRB 980425 and SN 1998bw , and subsequently some SN light contribution was found in the late-time light curves of GRB 980326 (Castro-Tirado & Gorosabel 1999;Bloom et al 1999), GRB 970228 , and GRB 970508 (Sokolov 2002), as well as possibly GRB 980703 ), GRB 990712 (Björnsson et al 2001, GRB 991208 (Castro-Tirado et al 2001), and GRB 000911 (Lazzati et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, X-ray flashes, which are associated to long-duration GRBs, are probably produced by the highlyrelativistic jets ejected in core-collapse supernova explosions. The relativistic fireball model (Goodman 1986;Paczyński 1986Paczyński , 1990Castro-Tirado et al 2001) provides a reasonable description of the observed afterglow spectrum, which is produced by the synchrotron emission of electrons accelerated in a relativistic shock with an estimated total energy budget roughly the same order of magnitude as that of supernovae Ib/c (Frail 2001). The discovery of the slowly fading X-ray emission, from optical and radio afterglows of GRBs and the identification of host galaxies at cosmological distances provided additional support for their progenitors being produced short-lived massive stars at different cosmological epochs, whose detection is limited by the BATSE threshold to within distances slightly larger than z ∼ 4 (Wijiers et al 1997;Blain & Natarajan 2000).…”
Section: Introductionmentioning
confidence: 99%